The efficacy and safety of Dachaihu decoction in the treatment of nonalcoholic fatty liver disease: a systematic review and meta-analysis - Mou, Zhiqing; Gong, Tao; Wu, Yanzuo; Liu, Jun; Yu, Jianhua; Mao, Lichan (Frontiers in Medicine, 2024)
Background Nonalcoholic fatty liver disease (NAFLD), also known as metabolic associated fatty liver disease (MAFLD), is a common liver condition characterized by excessive fat accumulation in the liver which is not caused by alcohol. The main causes of NAFLD are obesity and insulin resistance. Dachaihu decoction (DCHD), a classic formula in traditional Chinese medicine, has been proved to treat NAFLD by targeting different aspects of pathogenesis and is being progressively used in the treatment of NAFLD. DCHD is commonly applied in a modified form to treat the NAFLD. In light of this, it is imperative to conduct a systematic review and meta-analysis to assess the effectiveness and safety of DCHD in the management of NAFLD. There is a need for a systematic review and meta-analysis to assess the effectiveness and safety of modified DCHD in treating NAFLD. Objective The objective of this meta-analysis was to systematically assess the clinical effectiveness and safety of DCHD in treating NAFLD. Methods This meta-analysis adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Including seven databases, both Chinese and English databases were searched for relevant studies. The quality of included studies was carefully assessed using the bias risk assessment tool in the Cochrane Handbook. Eligible articles were the source of extracted data which was meta-analyzed by using Review Manager 5.4 and Stata 17.0. Results A total of 10 studies containing 825 patients were included. Compared with conventional treatments, combined treatment could clearly improve the liver function of NAFLD patients, which could reduce the levels of ALT (MD = −7.69 U/L, 95% CI: −11.88 to −3.51, p < 0.001), AST (MD = −9.58 U/L, 95% CI: −12.84 to −6.33, p < 0.01), and it also had a certain impact on regulating lipid metabolism, which could reduce the levels of TC (MD = −0.85 mmol/L, 95% CI: −1.22 to 0.48, p < 0.01), TG (MD = −0.45 mmol/L, 95% CI: −0.64 to 0.21, p < 0.01). Adverse event showed that DCHD was relatively safe. Due to the inclusion of less than 10 trials in each group, it was not possible to conduct a thorough analysis of publication bias. Conclusion According to the meta-analysis, in the treatment of the NAFLD, it is clear that the combination of DCHD was advantages over conventional treatment alone in improving liver function, regulating lipid metabolism. Additionally, DCHD demonstrates a relatively safe profile. Nevertheless, due to limitations in the quality and quantity of the studies incorporated, the effectiveness and safety of DCHD remain inconclusive. Consequently, further high-quality research is imperative to furnish more substantial evidence supporting the widespread clinical application of DCHD. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023397353, CRD42023397353.